(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Adoption of decrees and resolutions of the Government of the Republic of Uzbekistan creates the legal basis for the cotton industry. It is also known that the priority task of the state is to improve and accelerate the work in the field of selection, seed, variety renewal, introduction of high-fiber cotton, early maturing varieties and their rational placement in different soil and climatic conditions of the country.